RUNNING TIME ALGORITMA SEARCHING DATA PADA ARRAY SATU DIMENSI MENGGUNAKAN JAVA NETBEANS - jOHNSON SIHOMBING (INFOKOM (Informatika & Komputer), 2018)
Data search algorithms are often used in any programming consisting of: sequential searching, binary searching and interpolation searching. Search data can be done in an array, either one-dimensional array, two dimensional and even n-dimensional. For the research, the author only do the implementation of search algorithm on a one dimensional array that each data element is numeric type. The search process is performed on consecutive and non-sequential data in the array. Unassisted data can be found in sequential searches. The opposite is true for binary search and interpolation search. The purpose of implementing the algorithm is to show the difference of the result of the running time of the three search algorithms above, which can be visualized in graphical form. The results are obtained after the authors perform the implementation of search algorithm by using a desktop-based Java software with editor or compiler Netbeans 8.1.